FORMULASI MASKER EKSTRAK DAUN PEPAYA (CARICA PAPAYA L.) SEBAGAI ANTI JERAWAT DAN AKTIVITASNYA TERHADAP PERTUMBUHAN BAKTERI PROPIONIBACTERIUM ACNES - Fahma Shufyani (Jurnal Bidan Mandira Cendikia, 2022)
Acne is an infection caused by the bacteria Propionibacterium acnes, Staphylococcus epidermidis and Staphylococcus Aureus with symptoms of inflammation in the facial area. Acne is a social disease that often occurs in adolescence and adulthood. Acne can be treated using antibiotics by considering the side effects on body systems and organ functions. Purpose of this study was to make and evaluate anti-acne cream preparations and their activity against Propionibacterium acnes bacteria. This research is a quasi-experimental type of research with before and after the experiment. In this study, observations and organoleptic tests were carried out before and after to see the effect of giving the sample extract on the bacteria Propionibacterium acnes.the results showing that papaya leaf extract (Carica Papaya L.) can inhibit the growth of the bacteria Propionibacterium acnes can be done with the diameter of the inhibition zone using a caliper for the bacteria Propionibacterium acnes which is fermented from NA to produce a yellow pigment which indicates the growth of bacteria Propionibacterium acnes on the media, where Bacterial colonies will grow around the yellow zone. Each petri dish was then added with NA media (Sodium Agar) and propionibacterium acnes suspension, the concentration was observed after the petri dish was incubated in the incubator for 24 hours at 37cC. After being observed, it turned out that all petri dishes at each concentration showed a clear zone around the concentration of papaya leaf extract (Carica Papaya L.).